2019
DOI: 10.1111/vru.12813
|View full text |Cite
|
Sign up to set email alerts
|

Norwich terriers possess a greater vertebral heart scale than the canine reference value

Abstract: Previous studies have demonstrated evidence that normal reference ranges for radiographic vertebral heart scale values can vary among dog breeds. The purpose of this retrospective, observational study was to determine whether the normal vertebral heart scale values published by Buchanan and Bücheler for lateral radiographs are applicable to the Norwich terrier. Secondary objectives were to determine if clinical signs of respiratory disease, age, sex, weight, body condition score, recumbency, or thoracic depth‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…For intraobserver and interobserver measurement agreement, VLAS and VHS showed an almost perfect agreement. This finding provides evidence that VLAS and VHS are repeatable methods for measuring cardiac chamber size, as confirmed by previous studies 10,11,13 . Further studied are needed to verify if veterinarians with different clinical experience and specialization (eg, general practitioners, cardiologists, intensive care clinicians) have the same measurement variability.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For intraobserver and interobserver measurement agreement, VLAS and VHS showed an almost perfect agreement. This finding provides evidence that VLAS and VHS are repeatable methods for measuring cardiac chamber size, as confirmed by previous studies 10,11,13 . Further studied are needed to verify if veterinarians with different clinical experience and specialization (eg, general practitioners, cardiologists, intensive care clinicians) have the same measurement variability.…”
Section: Discussionsupporting
confidence: 84%
“…First, the possible influence of the body condition score on VLAS was not evaluated. Previous studies have reported the possible influence of body condition score on VHS 7,9,11 . However, all dogs included in the study were healthy, and no obese or cachectic dogs were present in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Previous studies have highlighted interbreed VHS differences, establishing that the VHS reference ranges of some breeds significantly differ to those proposed by Buchanan and Bucheler. [5][6][7][9][10][11][12][13][14][15] Consequently, the previously established mean normal value of 9.7 ± 0.5 vertebrae cannot be applied to all canine breeds.…”
Section: Discussionmentioning
confidence: 99%
“…4 The VHS is influenced by different breed-specific morphotypes, and several studies have described a breed-specific reference range for the VHS. [5][6][7][8][9][10][11][12][13][14][15] The vertebral left atrial size (VLAS) has recently been proposed as a new radiographic method for the evaluation of left atrial size in dogs 16 ; however, no studies have evaluated VLAS variations in relation to different breeds. The Chihuahua is predisposed to the development of both congenital and acquired cardiac disease.…”
Section: Introductionmentioning
confidence: 99%